The Face of Mountainous Islam: The Dynamic of Islam in the Dieng Mountains Wonosobo, Central Java, Indonesia - Ahmad Salehudin; Moch. Nur Ichwan; Dicky Sofjan (UIN Sunan Kalijaga Yogyakarta, 2017)
This article elaborates Mountainous Islam in the Dieng Mountains. Today Dieng is a Muslim society. However the historical accounts about the way Islam entered Dieng are still debatable. It becomes more difficult since there is no any support data that is quite reliable. Based on oral history and Islamic phenomenon, there are three important finding showed. First, the history of Islam in the Dieng Mountains is provided clear information that Islam entered to the Dieng not merely by the acculturation process as commonly understood, but also colonialization. Second, the Islamic tradition in the Dieng Mountains is the result of the negotiation of Islamic traditions and Hindu-Buddhist that first grew in Dieng, and present traditions that come to the Dieng Mountains. Islam Dieng creatively adopts and adapts new traditions in line with the improvement of society’s economic condition. Third, Islamic expression displayed by the Dieng community is a portrait of a mountainous Islam that is adaptive, dynamic, and open to change. Their religious expression will continue to change along with the development of creativity that is influenced by economic development, educational attainment, their encounters with outsiders, and the natural vulnerabilities they face as people living in active and often life-threatening mountains.[Artikel ini menguraikan Islam Pegunungan di Dieng. Hari ini Dieng adalah sebuah masyarakat Muslim. Namun catatan sejarah tentang cara masuknya Islam Dieng masih diperdebatkan. Ini menjadi lebih sulit karena tidak ada data pendukung yang cukup andal. Berdasarkan sejarah lisan dan fenomena Islam, ada tiga temuan penting yang ditunjukkan. Pertama, sejarah Islam di Pegunungan Dieng memberikan informasi yang jelas bahwa Islam masuk ke Dieng tidak hanya dengan proses akulturasi seperti yang biasa dipahami, tapi juga kolonialisasi. Kedua, tradisi Islam di Pegunungan Dieng adalah hasil negosiasi tradisi Islam dan Hindu-Budha yang datang pertama kali ke Dieng. Islam Dieng secara kreatif mengadopsi dan menyesuaikan dengan dan menciptakan tradisi baru seiring dengan membaiknya kondisi ekonomi masyarakat. Ketiga, ekspresi Islam yang ditampilkan oleh masyarakat Dieng merupakan potret sebuah agama Islam pegunungan yang adaptif, dinamis, dan terbuka untuk berubah. Ekspresi religius mereka akan terus berubah seiring dengan perkembangan kreativitas yang dipengaruhi oleh pembangunan ekonomi, pencapaian pendidikan, perjumpaan mereka dengan orang luar, dan kerentanan alami yang mereka hadapi sebagai orang yang tinggal di pegunungan yang aktif dan sering mengancam jiwa.]